2020
DOI: 10.1002/adma.202003493
|View full text |Cite
|
Sign up to set email alerts
|

Gradient‐Concentration Design of Stable Core–Shell Nanostructure for Acidic Oxygen Reduction Electrocatalysis

Abstract: Article type: Communication Gradient-concentration design of stable core-shell nanostructure for acidic oxygen reduction electrocatalysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 43 publications
3
60
0
Order By: Relevance
“…Non-Noble Metals (Fe, Ni, Cu, Sn): Fe (Downshift of ε d ): Construction of holes on the carbon substrate induces the favorable manipulation of the electronic structures of the Fe-N 4 sites for the Fe-N-G-p electrocatalyst, as reported by Li et al [190] The unique configurations of the Fe-N-G-p electrocatalyst cause the downshift of the d-band center, which weakens the bonding strength between the * CO intermediates and the active sites (Figure 18a). DFT-based calculations Pt 75 Co 25 /C(500) None 2.06@0.9 V versus RHE 0.97@0.9 V versus RHE 0.1 m HClO 4 Pt Downshift [180] PtML IrNi/C None ≈0.6@0.9 V versus RHE ≈1.35@0.9 V versus RHE 0.1 m HClO 4 Pt Downshift [181] PtNiRu-IL/C None 2.26@0.9 V versus RHE 1.31@0.9 V versus RHE 0.1 m HClO 4 Pt Downshift [182] Pt/BC None 7.1@0.9 V versus RHE 0.209@0.9 V versus RHE 0.1 m HClO 4 Pt [111] PtCu/C 0.942 0.42@0.9 V versus RHE 1.2@0.9 V versus RHE 0.1 m HClO 4 Pt Upshift [183] PtNi-BNCs/C None 5.16@0.9 V versus RHE 3.52@0.9 V versus RHE 0.1 m HClO 4 Pt Downshift [169] TePtCo 0.924 1.15@0.9 V versus RHE 0.7@0.9 V versus RHE 0.1 m HClO 4 Pt Downshift [184] Pt/22L-Ti 3 C 2 None 0.1@0.9 V versus RHE 0.04@0.9 V versus RHE 0.1 m HClO 4 Pt Downshift [107] Pt-Ni@PtD/G 0.829 0.098@0.9 V versus RHE 0.061@0.9 V versus RHE 0.1 m HClO 4 Pt Ni Upshift [89] reveal the facile desorption of the * CO from the catalyst surface, which offers more fresh sites for the generation of CO, and thus accelerates the reaction kinetics. The electrocatalytic performance for the Fe-N-G-p indicates a high FE of 94% with a CO partial current density of 4.5 mA cm -2 at the potential of −0.58 V versus RHE and a high TOF value of 1630 h -1 (Figure 18b).…”
Section: Ag (Upshift Of ε D )mentioning
confidence: 99%
“…Non-Noble Metals (Fe, Ni, Cu, Sn): Fe (Downshift of ε d ): Construction of holes on the carbon substrate induces the favorable manipulation of the electronic structures of the Fe-N 4 sites for the Fe-N-G-p electrocatalyst, as reported by Li et al [190] The unique configurations of the Fe-N-G-p electrocatalyst cause the downshift of the d-band center, which weakens the bonding strength between the * CO intermediates and the active sites (Figure 18a). DFT-based calculations Pt 75 Co 25 /C(500) None 2.06@0.9 V versus RHE 0.97@0.9 V versus RHE 0.1 m HClO 4 Pt Downshift [180] PtML IrNi/C None ≈0.6@0.9 V versus RHE ≈1.35@0.9 V versus RHE 0.1 m HClO 4 Pt Downshift [181] PtNiRu-IL/C None 2.26@0.9 V versus RHE 1.31@0.9 V versus RHE 0.1 m HClO 4 Pt Downshift [182] Pt/BC None 7.1@0.9 V versus RHE 0.209@0.9 V versus RHE 0.1 m HClO 4 Pt [111] PtCu/C 0.942 0.42@0.9 V versus RHE 1.2@0.9 V versus RHE 0.1 m HClO 4 Pt Upshift [183] PtNi-BNCs/C None 5.16@0.9 V versus RHE 3.52@0.9 V versus RHE 0.1 m HClO 4 Pt Downshift [169] TePtCo 0.924 1.15@0.9 V versus RHE 0.7@0.9 V versus RHE 0.1 m HClO 4 Pt Downshift [184] Pt/22L-Ti 3 C 2 None 0.1@0.9 V versus RHE 0.04@0.9 V versus RHE 0.1 m HClO 4 Pt Downshift [107] Pt-Ni@PtD/G 0.829 0.098@0.9 V versus RHE 0.061@0.9 V versus RHE 0.1 m HClO 4 Pt Ni Upshift [89] reveal the facile desorption of the * CO from the catalyst surface, which offers more fresh sites for the generation of CO, and thus accelerates the reaction kinetics. The electrocatalytic performance for the Fe-N-G-p indicates a high FE of 94% with a CO partial current density of 4.5 mA cm -2 at the potential of −0.58 V versus RHE and a high TOF value of 1630 h -1 (Figure 18b).…”
Section: Ag (Upshift Of ε D )mentioning
confidence: 99%
“…[113] Lyu et al reported the gradient alloying of PtNi alloy with Pt-rich skin. [114] Then, the researchers applied acid leaching to partially dealloy the minor nickel atoms on the surface to generate defective Pt-rich skeleton shell. A surfactant-modified HNO 3 dealloying approach was also developed to obtain {111} and {100} facets and step/kink sites enriched nanoporous Au with the assistance of pyrogallol and sodium citrate, respectively.…”
Section: (De)alloyingmentioning
confidence: 99%
“…One of the important points that is limiting the use of bimetallic catalysts is the leaching of the alloying component, which results in the poisoning of the proton-exchange membrane and the degradation of the membrane electrode assembly (MEA) [7,8]. Therefore, one of the current research areas of the present paper is the catalyst's synthesis with nanoparticles of the following structures: core-shell [4,[9][10][11], gradients [12,13], hollow [14][15][16], porous frameworks [17,18], nanowires, and nanodendrites [19][20][21]. The key components of such catalysts are nanoparticles with a platinum shell, which protects the d-metal core from dissolution during the fuel cell operation.…”
Section: Introductionmentioning
confidence: 99%